Avaliação da capacidade adsortiva do ZIF-8 para remoção de óleo em águas produzidas - Estrela Filho, Otoniel Anacleto (2023)
The considerable amount of produced water discharged by the oil industry contributes to an environmental imbalance, due to the presence of several potentially harmful components to the ecosystem. Among remediation techniques, adsorption is widely investigated because of its adaptability and efficiency. Zinc Imidazolate Framework-8 (ZIF-8) has properties such as a high surface area, adjustable pore sizes and hydrophobicity, which give it a high capacity for adsorbing hydrocarbons. This study aims to investigate ZIF-8 as an adsorbent for oil removal in synthetic produced water by finite bath systems. To identify the ZIF-8 phases, their constitutional groups, their morphological, textural and thermal properties, the synthesized material, by the solvothermal method, was characterized by ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TG/DTG/DSC), surface area and porosity analysis by the BET method, in addition to determining its point of zero charge (pHpcz). The factors that influence the adsorption capacity were verified, such as pH, mass of the adsorbent, contact time and temperature. From the results of DRX and FTIR, it was possible to confirm the synthesis of pure ZIF-8. The adsorbent showed thermal stability up to 400 °C, surface area of 1558.1 m2.g and average pore diameter equal to 28.8 nm. The pseudo-first order model (PPO) was the most representative and the adsorption process, according to the intraparticle diffusion model, presents multilinearity. The experimental equilibrium data fit better to the Sips model, indicating that the process takes place in a heterogeneous system. The thermodynamic study showed that the adsorption process is spontaneous and exothermic, being a physisorption. Thus, ZIF-8 showed properties that enable its use in the adsorption of oil, which had an adsorption capacity equal to 462.8 mg.g1, where the interactions between adsorbate and adsorbent is based on electrostatic and hydrophobic interactions. Thus, the efficient removal of oil by ZIF-8 makes it promising in the adsorption process in an oil/water separation system.